Floor Area Ratio (FAR) and Sustainable Urban Living Observing Data Using Urban Modeling Interface (UMI) Case Yogyakarta Indonesia - Pamungkas, Luhur Sapto; Kusumawanto, Arif; Marsoyo, Agam (International Journal of Science, Technology & Management, 2023)
Floor area ratio (FAR) is a measurement, expressed as a decimal, that describes the total amount of usable floor space in a building compared to the size of the lot that the building is on. FAR using by building planner to maintain development standards and guide or restrict the development of local communities. In many cases FAR is an element of sustainability in urban environments so that residents are able to survive in a limited land environment. The FAR value is set locally by the local government. This research was conducted in one of block area of the urban in the center city of Yogyakarta, namely Malioboro. The measurement results with the urban modeling interface (UMI) software show that urban living in this area has a FAR value below the existing reference standard of 4.00. Averarge FAR is 1.125. This means that the formations of urban living still very suitable for habitation. It could be that the FAR value of 4 is a long-term orientation to maintain the quality quality of urban living dan sustainability.